The Role of Organizational Structure, Efficacy and Trust as Antecendents of Employee Performance - Selly Marlina; Nancy Yusnita; Yayan Hadiyat (Asosiasi Ahli Administrasi Indonesia, 2026)
This study aims to analyze the influence of organizational structure and self-efficacy on employee performance with trust as an intervening variable in the Cianjur Regency Manpower and Transmigration Office. The phenomenon of fluctuating and suboptimal performance achievement encourages the importance of a comprehensive understanding of the interaction of structural, psychological, and relational factors in public organizations. The study used a quantitative approach with a total sampling of all active employees. Data were collected through a Likert scale questionnaire and analyzed using path analysis and Sobel test to test the effects of mediation. The results of the study show that organizational structure has a direct effect on performance but not on trust. Self-efficacy has a significant effect on confidence but does not have a direct effect on performance. Trust has proven to be the most dominant predictor and mediates the relationship between self-efficacy and performance. These findings confirm that optimizing employee performance requires an integrative approach that balances structural system improvement with strengthening trust-based social capital to improve the quality of public services.